Maritime Disputes in the Eastern Mediterranean : The Way Forward - Baroudi, Roudi (Book collections on Project MUSE., 2020)
The ways and means described in this book constitute a road map for responsible members of the international community to work together, reduce tensions, resolve differences over maritime boundaries peacefully, and reap the rewards of a safer, stabler, and more prosperous world. This volume shows that the UN and its associated treaties, courts, and other institutions have developed a body of laws, rules, and procedures guiding the way to negotiated, peaceful outcomes. Mr. Baroudi's book also points to rapid advances of science and technology that take much of the guesswork out of boundary delineation, making this route more reliable and user-friendly than ever before. The successful use of these mechanisms would set a useful example for the resolution of boundary disputes in other regions of the world. That, in turn would restore confidence in the international rules-based system and could pave the way for the settling of some of the world's most troubling and dangerous disputes.